An An Assessment of the Efficacy of Chlorhexidine in Nebulizer Disinfectant to Prevent Contaminated Aerosol Administration - Rustiana Tasya Ariningpraja; Shila Wisnasari; Ahsan Ahsan; Heri Kristianto; Luis Figo Febriano (Fakultas Farmasi Universitas Andalas, 2025)
Nebulization therapy is an essential method of drug administration that enables effective delivery of medicationsto the respiratory tract in aerosol form; however, contaminated nebulizer components may serve as a source of pathogenicmicroorganisms associated with nosocomial pneumonia. This in vitro experimental study aimed to evaluate the effectiveness ofchlorhexidine as a nebulizer disinfectant in eliminating pathogenic bacteria. The study employed a post-test control group designusing six groups of nebulizer chambers, consisting of two control groups and four intervention groups. Two clinically relevantbacteria, Pseudomonas aeruginosa and Acinetobacter baumannii, were inoculated into the nebulizer chambers. The interventiongroups were disinfected using chlorhexidine gluconate at concentrations of 2.5%, 4%, and 5% diluted in 70% alcohol, and 2.5%chlorhexidine diluted in distilled water, while the control groups received sterile water and 70% alcohol, in accordance withexisting guidelines. After a standardized exposure period, bacterial growth was assessed using Colony Forming Unit (CFU) counts. Data were analyzed descriptively and comparatively to evaluate bacterial eradication across groups. The results demonstrated that 5% chlorhexidine diluted in 70% alcohol achieved complete bacterial elimination (0 CFU) for both bacterial strains, whereas lower concentrations showed residual growth. These findings indicate that chlorhexidine, particularly at higher concentrations, demonstrates strong disinfectant activity against common nosocomial pneumonia pathogens in nebulizer chambers. Nevertheless, the results are limited to in vitro conditions; therefore, further studies involving a wider range of microorganisms, standardized exposure times, and assessments of aerosol contamination during clinical nebulization are warranted to support its practical application.